Penerapan Problem Based Learning dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII dengan Menggunakan Media Quizizz Paper Mode - Kurniatin; Sudi Prayitno; Dwi Aprilia Anggraeni (Mataram University, 2026)
This study aimed to improve the mathematics learning outcomes of eighth-grade students in class VIII-B at SMPN 11 Mataram through the implementation of the Problem-Based Learning (PBL) model supported by Quizizz Paper Mode media. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. The research subjects were 28 students of class VIII-B in the odd semester of the 2024/2025 academic year. Data were collected using mathematics learning outcome tests, while data analysis was carried out descriptively. The indicator of research success was determined based on the achievement of the Minimum Mastery Criteria (KKM) of 67 with a minimum classical mastery of 85%. The results showed that in the pre-cycle stage, the students’ average score was 54 with a mastery level of 29%. In Cycle I, the average score increased to 64 with a mastery level of 64%. Furthermore, in Cycle II, the students’ average score increased significantly to 89, with classical mastery reaching 89%. These findings indicate that the implementation of the Problem-Based Learning model supported by Quizizz Paper Mode media was effective in improving students’ mathematics learning outcomes on the topic of the Pythagorean Theorem.